2020
DOI: 10.1148/radiol.2020202348
|View full text |Cite
|
Sign up to set email alerts
|

Lower-extremity Arterial Thrombosis Associated with COVID-19 Is Characterized by Greater Thrombus Burden and Increased Rate of Amputation and Death

Abstract: C oronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is characterized by the respiratory symptoms implicit in the name severe acute respiratory syndrome. Still, with the increasing number of cases, it has also been linked to nonpulmonary targets, including cardiac, gastrointestinal, skin, renal, and neurologic manifestations (1-5). Venous thromboembolism has also been shown to be an important cause of morbidity and mortality in patients with COVID-19, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
98
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 26 publications
6
98
0
4
Order By: Relevance
“…In the absence of any evidence of cardiac source we speculate that the thrombus formation is occurring in the setting of a hypercoagulable state and is most likely in the form of large-vessel mural thrombus formation. This is similar to what was seen by Goldman et al in the cases they described 6 . A paradoxical embolus (venous thrombosis with a patent foramen ovale) is another possibility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the absence of any evidence of cardiac source we speculate that the thrombus formation is occurring in the setting of a hypercoagulable state and is most likely in the form of large-vessel mural thrombus formation. This is similar to what was seen by Goldman et al in the cases they described 6 . A paradoxical embolus (venous thrombosis with a patent foramen ovale) is another possibility.…”
Section: Discussionsupporting
confidence: 92%
“…Study by Goldman et al demonstrated an association between COVID-19 and lower extremity arterial thrombosis with greater thrombus burden characterized by predilection for proximal arteries 6 . They suggested that COVID-19 is associated with lower extremity arterial thrombosis characterized by greater clot burden and a direr prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…respectively. 6,36 This amputation rate is higher than in patients with acute arterial thrombosis without COVID-19 infection reported in the USA and England. 37,38 Our high amputation rate could be explained because of elevated number of patients with severe COVID-19 infection (53.3%) and…”
Section: Discussionmentioning
confidence: 81%
“…A recent study comparing 16 patients with COVID-19 (age 70 ± 14 years, 7 women) undergoing lower extremity CT angiogram (CTA) with 32 propensity-score matched control patients (age 71 ± 15 years, 16 women), showed that all COVID-19 patients had at least 1 arterial thrombus while only 69% of controls had arterial thrombi (p = 0.02); proximal thrombi were present in 94% of COVID-19 patients compared with 47% of controls (p < 0.001). 35 Death or limb amputation was more common in COVID-19 patients (odds ratio-OR 25, p < 0.001).…”
Section: Other Systemic Thrombosis/thromboembolismmentioning
confidence: 98%